The Bukidnon worldview as reflected by the metaphors in a voice from the hill (written by Francisco Col-on Polenda and translated by Richard Elkins) - Rubin, Krissi Shaffina Twyla A. (College of Arts and Letters, University of the Philippines Diliman, 2002)
The collection of essays by Franciso Col-on Polenda, translated by Richard Elkins, entitled "A Voice from the Hills", explains the worldview of the Western Bukidnon Manobo. This research uses the metaphors employed in the essays as windows through which to tap the rich culture of Bukidnon. The analysis of the different terms, symbolizations, and representations in the metaphors in the text reveal the core aspect of the Bukidnon culture, which is its belief in the supernatural and the spirituality of the people. Interviews with reliable informants like Datu Inlantong and Datu Macabugwas and the aid of other Bukidnon texts contextualize the occurrence of particular metaphors and dominant images in the text. Moreover, the consistency of the translated text with the Bukidnon informants and other Bukidnon texts further attest to the validity and reliability of Elkin's translation.